-16k+56 check photo for steps and please mark as brainliest if i helped! thanks c:
2 plus 2 plus 2 = 6 divid it By 3 which equals 2
Answer:
(1,-4) and (0,2)
Step-by-step explanation:
Answer:
B. (13√2)/2
Step-by-step explanation:
Let L represent the length of one leg of the triangle. We note that the triangle is isosceles, so both legs are the same length. Then the Pythagorean theorem tells you the square of the hypotenuse is the sum of the squares of the legs:
13² = L² + L²
13² = 2L²
13 = (√2)L
L = 13/√2 = (13√2)/2 . . . length of one leg
_____
To "rationalize the denominator", we multiply the fraction 13/√2 by (√2)/(√2). The result is (13√2)/2.